2018
DOI: 10.1136/bmjsem-2017-000331
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preoperative and postoperative resistance exercise interventions on recovery of physical function in patients undergoing abdominal surgery for cancer: a systematic review of randomised controlled trials

Abstract: ObjectiveTo systematically review the effects of preoperative and postoperative resistance exercise training on the recovery of physical function in patients undergoing abdominal surgery for cancer.Data sourcesA systematic review of English articles using Medline, Physiotherapy Evidence Database, CINAHL and the Cochrane Library electronic databases was undertaken.Eligibility criteria for selecting studiesStudies were included if they used a randomised, quasi-randomised or controlled trial study design and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Prehabilitation in the form of preoperative exercise intervention was initially of interest in cardiothoracic surgery but is also being investigated in abdominal surgery. Since 2013, at least 13 systematic reviews of studies of prehabilitation in abdominal or cancer surgery have been published [22][23][24][25][26][27][28][29][30][31][32][33][34] . These interventions are mostly comprised of one or all of the following elements: inspiratory muscle training with the aim of reducing postoperative pulmonary complications (PPCs), aerobic exercise training (which can be low or high intensity, supervised or unsupervised), and muscle strengthening or resistance training.…”
Section: Exercise Interventionmentioning
confidence: 99%
“…Prehabilitation in the form of preoperative exercise intervention was initially of interest in cardiothoracic surgery but is also being investigated in abdominal surgery. Since 2013, at least 13 systematic reviews of studies of prehabilitation in abdominal or cancer surgery have been published [22][23][24][25][26][27][28][29][30][31][32][33][34] . These interventions are mostly comprised of one or all of the following elements: inspiratory muscle training with the aim of reducing postoperative pulmonary complications (PPCs), aerobic exercise training (which can be low or high intensity, supervised or unsupervised), and muscle strengthening or resistance training.…”
Section: Exercise Interventionmentioning
confidence: 99%
“…The evaluation showed that the Activity Board resulted in a higher level of mobilisation in the group with the Activity Board compared with the group who received standard treatment [19]. Although evidence for exercise after abdominal surgery is scarce [20], a few studies have evaluated exercise programmes for patients postoperatively at the hospital ward with promising results [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…1 Although it is recognized in the early stages of cancer recovery that changes in lifestyle including increasing physical activity can help to improve overall well-being, there are is very little clinical evidence in terms of how different modes of physical function and modes of exercise can be incorporated following active cancer treatment. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…The methodological quality of these randomized studies are moderate, with unclear bias, difficulty in blinding trial participants and therapists, and in respect to description of the intervention, some information lacking in terms of equipment and methodology with regard to aerobic and functional activity components. 2 Resistance exercise (or strength) training could help to facilitate recovery of muscle function. 16 In particular isometric resistance (or static) training has been used in the rehabilitation of weak or atrophied muscle following surgery; 17 important factors to be considered in establishing an effective training regime include the training intensity, the number and durations of voluntary contractions, and the number and frequency of training sessions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation